Kinetic Studies and Mechanism of Hydrogen Peroxide Catalytic Decomposition by Cu(II) Complexes with Polyelectrolytes Derived from L-Alanine and Glycylglycine - Spyridon Skounas; Constantinos Methenitis; George Pneumatikakis; Michel Morcellet (Bioinorganic Chemistry and Applications)
The catalytic decomposition of hydrogen peroxide by Cu(II) complexes with polymers bearing L-alanine (PAla) and glycylglycine (PGlygly) in their side chain was studied in alkaline aqueous media. The reactions were of pseudo-first order with respect to [H2O2] and [L-Cu(II)] (L stands for PAla or PGlygly) and the reaction rate was increased with pH increase. The energies of activation for the reactions were determined at pH 8.8, in a temperature range of 293–308 K. A suitable mechanism is proposed to account for the kinetic data, which involves the Cu(II)/Cu(I) redox pair, as has been demonstrated by ESR spectroscopy. The trend in catalytic efficiency is in the order PGlygly>PAla, due to differences in modes of complexation and in the conformation of the macromolecular ligands.